Enhancement of Oleic Acid in Butter Oil by High Oleic Fraction of Moringa oleifera Oil: Moringa oleifera for Butter Oil Enhancement - Nadeem, Muhammad; Ullah, Rahman (Biological Sciences - PJSIR, 2016)
Oleic acid in butter oil (BO) was enhanced by a high oleic acid fraction (HOF) of Moringa oleifera oil (MOO). HOF was blended with BO at four different concentrations i.e. 5%, 10%, 15% and 20% (HOF-5, HOF-10, HOF-15 and HOF-20, respectively), compared with a control (BO). The oleic acid in HOF increased from 71.55% to 80.25%. DPPH free radical scavenging activity and total flavonoid content of HOF was 76.88% and 34.52 mg/100 g. Supplemenation of butter oil with 20% HOF, decreased the cholesterol from 224 to 177 mg/100 g. Peroxide value of three months stored HOF-20 was 1.18 (meqO2/ kg) as compared to control, 3.15 (meqO2/kg). Induction period of HOF-20 was 4.07 h greater than control. These results evidenced that oleic acid in butter oil can be substantially increased by HOF of MOO.